A precise theoretical method for high- throughput screening of novel organic electrode materials for Li-ion batteries - Wanwan Zhang; Pengkun Sun; Shaorui Sun (Journal of Materiomics, 2017)
Organic electrode materials have gained significant attention due to their flexibility, lightweight characteristics, abundant resources in nature, and low CO2 emission. It's urgently needed for setting up an accurate high-throughput screening theoretical scheme that could find out possible candidates of electrode materials. Currently, the error between the theoretical potentials calculated by the PBE-D2 (DFT-D2, dispersion-corrected density functional theory) method and the experimental values is larger than 12%. Thus, it's essential to finding a more accurate method. In the present work, hybrid functionals and vdW correction methods are applied to investigate six reported organic electrode materials for Li-ion batteries. The results show that the hybrid functional combined with the D2 dispersion corrected method, i.e., HSE06-D2 (Heyd, Scuseria, and Ernzerhof, dispersion-corrected), is able to predict the potential of the organic material precisely with an average error of approximately 5%. This method occupies much hardware resources and being very time consuming, but it could be applied as the final ultrafine step in the high-throughput screening program.